Effects of residual suction and residual water content on the estimation of permeability function - Zhai, Qian (2017)
Soil-water characteristic curve (SWCC), which defines the relationship between water amount in the soil and matric suction, contains key information for the application of unsaturated soil mechanics principles to engineering practice. Best fit equations are commonly used for representation of the SWCC for unsaturated soils. Normally, these best fit equations are mathematically continuous and governed by a few fitting parameters. Either volumetric water content, θw or normalized volumetric water content, Θ, is adopted in the different best fit equations. If θw is used to establish SWCC, the parameter related to residual suction, Cr needs to be defined prior to fitting process of SWCC data. On the other hand, if Θ is used to develop SWCC, the residual volumetric water content, θr, needs to be defined prior to fitting process of SWCC data. Results of analyses in this study indicate that the performance of the best fit equation is not affected by the value of Cr, but it is significantly affected by the value of θr. As a result, the performance on the estimation of the permeability function is also affected by the value of θr. Different types of soils are used to investigate the effect of Cr and θr on the performance of the best fit equation and the estimation of the permeability function.